Enhanced production of recombinant proteins in Corynebacterium glutamicum by constructing a bicistronic gene expression system - Manman Sun; Xiong Gao; Zihao Zhao; An Li; Yali Wang; Yankun Yang; Xiuxia Liu; Zhonghu Bai (Microbial Cell Factories, 2020)
Abstract Background Corynebacterium glutamicum is a traditional food-grade industrial microorganism, in which an efficient endotoxin-free recombinant protein expression factory is under developing in recent years. However, the intrinsic disadvantage of low recombinant protein expression level is still difficult to be solved. Here, according to the bacteria-specific polycistronic feature that multiple proteins can be translated in one mRNA, efforts have been made to insert a leading peptide gene upstream of target genes as an expression enhancer, and it is found that this can remarkably improve the expression level of proteins under the control of inducible tac promoter in C. glutamicum. Results In this research, the Escherichia coli (E. coli) tac promoter combined with 24 different fore-cistron sequences were constructed in a bicistronic manner in C. glutamicum. Three strong bicistronic expression vectors were isolated and exhibited high efficiency under different culture conditions. The compatibility of these bicistronic vectors was further validated using six model proteins- aldehyde dehydrogenase (ALDH), alcohol dehydrogenase (ADH), RamA (regulator of acetate metabolism), Bovine interferon-α (BoIFN-α), glycoprotein D protein (gD) of infectious bovine rhinotracheitis virus (IBRV) and procollagen type Ι N-terminal peptide (PΙNP). All examined proteins were highly expressed compared with the original vector with tac promoter. Large-scale production of PΙNP was also performed in fed-batch cultivation, and the highest PΙNP production level was 1.2 g/L. Conclusion In this study, the strength of the inducible tac promoter for C. glutamicum was improved by screening and inserting fore-cistron sequences in front of the target genes. Those vectors with bicistronic expression patterns have strong compatibility for expressing various heterogeneous proteins in high yield. This new strategy could be used to further improve the performance of inducible promoters, achieving double competence of inducible control and high yield.